Optimization of antibiotic selection in the emergency department for urine culture follow ups, a retrospective pre-post intervention study: clinical pharmacist efforts - Abdulaziz Saleh Almulhim; Ali Aldayyen; Kateryna Yenina; Adam Chiappini; Tahir Mehmood Khan (Taylor & Francis Group, 2019)
Introduction Urinary tract infections (UTI) are commonly encountered in the emergency department (ED). ED culture follow up is an important tool to provide the appropriate therapy after the identification of the causative pathogen. There is a growing body of evidence for the positive role of pharmacists in following up the ED cultures. The purpose of this study was to compare pharmacist driven urine culture follow ups to the nurse-practitioner (NP) driven follow ups in term of the appropriateness of antibiotic selections in patients with resistant isolates, inappropriately treated asymptomatic bacteriuria, and inappropriately chosen antibiotic. Methodology This was a retrospective pre-post intervention study divided into a two group period to compare pharmacist to NP led ED culture follow up interventions. Statistical Package for Social Sciences (SPSS) version 20 was used for analysis. Student's t-test was used for continuous variables and Chi-square test/or fisher's-exact test when appropriate were used for the primary outcome. Results Fifty-five patients (25.7%) and 102 (34%) met the inclusion criteria in the pharmacist arm and in the NP arm, respectively. Escherichia coli was the most commonly isolated pathogen in both arms. Asymptomatic bacteriuria was often treated in the ED in both groups (45/157, 28.7%) and there were no efforts in discontinuation of antibiotics in these patients. Neither the interventions group nor the no interventions groups were statistically different between the pharmacist and NP arms (P 0.0778), (P 0.797), respectively. Conclusion No statistically significant difference was observed between pharmacist driven monitoring and NP driven monitoring. In our institution, asymptomatic bacteriuria was commonly treated even in the absence of indications. We recommend that Pharmacists' roles in the ED cultures follow up be expanded to include antibiotic discontinuation in patients who meet asymptomatic bacteriuria criteria or have confirmed negative urine culture.